2003
DOI: 10.1021/ie020386h
|View full text |Cite
|
Sign up to set email alerts
|

Multivariable Control of a Simulated Industrial Gas-Phase Polyethylene Reactor

Abstract: A multivariable control problem of an industrial gas-phase polyethylene reactor is investigated in this paper. This multivariable control problem affects directly the polymer properties and consequently the plant economics. The control task is particularly challenging because of the two-time-scale behavior of the process and because of the multirate sampling of the process controlled variables. Two control schemes and two control algorithms are tested and compared. One control scheme considers the overall cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…In the operating range of industrial interest, the fluidized‐bed reactor in Figure can be modeled as a single‐phase, well‐mixed continuous stirred‐tank reactor . For simplicity, it is assumed that there is only one type of active catalyst sites . A mathematical model for this reactor has the form lefttrueitalicdYitalicdt=FcackdYRM1MW1+RM2MW2YBwitalicdTitalicdt=Hf+HgHitalictopHrHitalicpolMrCitalicpr+BwCitalicppolditalicInitalicdt=FitalicInxitalicInbtVgdM1italicdt=FM1xM1btRM1VgdM2italicdt=FM2xM2btRM2VgdHitalicdt=FHxHbtVgitalicdMIc13.5dt=1τritalicMIi13.51τritalicMIc13.5dDc1italicdt=1τr…”
Section: Case Studiesmentioning
confidence: 99%
“…In the operating range of industrial interest, the fluidized‐bed reactor in Figure can be modeled as a single‐phase, well‐mixed continuous stirred‐tank reactor . For simplicity, it is assumed that there is only one type of active catalyst sites . A mathematical model for this reactor has the form lefttrueitalicdYitalicdt=FcackdYRM1MW1+RM2MW2YBwitalicdTitalicdt=Hf+HgHitalictopHrHitalicpolMrCitalicpr+BwCitalicppolditalicInitalicdt=FitalicInxitalicInbtVgdM1italicdt=FM1xM1btRM1VgdM2italicdt=FM2xM2btRM2VgdHitalicdt=FHxHbtVgitalicdMIc13.5dt=1τritalicMIi13.51τritalicMIc13.5dDc1italicdt=1τr…”
Section: Case Studiesmentioning
confidence: 99%
“…The steady state operating conditions for the plant are given in Tables 2 and 3. These operating conditions were found by optimization and were discussed elsewhere [26].…”
Section: Process Modelmentioning
confidence: 99%
“…For nonlinear MPC, the predicted output, y over the prediction horizon P is obtained by the numerical integration of: (26) y=g(x) (27) from t k up to t k+P where x and y represent the states and the output of the model, respectively. The symbol ||.|| denotes the Euclidean norm, k is the sampling instant, Γ and Λ are diagonal weight matrices and R=[r(k+1) … r(k+P)] T is a vector of the desired output trajectory.…”
Section: The On-line Nlmpc Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…The controller exhibited greater performance and was able to maintain the stability over a wide range of operating conditions compared to optimally tuned PID controller. E. Ali et al (2003) [8] presented two control schemes in the paper to study the multivariable control of polyethylene in fluidized bed reactor where both nonlinear and linear MPC are used and compared. It was found that non-linear MPC was better than the latter in the sense providing a good performance even in the presence of moderate modeling error.…”
Section: Introductionmentioning
confidence: 99%